The Development of Solo Taxonomy Based Assessment Instrument on Human Respiratory System to Measure Thinking Skills and Mastery of Concepts - Putri, Pranutasani Parameswari; Raharjo, Raharjo (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2020)
Appraisal or assessment is the core of education process which create a series of data required for obtaining its level of achievement on the thinking process. The aim of thinking is ultimately developing its individual ability to learn and master the concept which both elements can be acknowledged and measured precisely by using the correct instrument. Those two elements are the essence of this literature to exhibit the ultimate goal of its research based on valid empirical and theoretical data to develop a concept of appraisal solo taxonomy instruments based on human respiratory system for measuring thinking ability and mastering concepts. The human respiratory system is selected due to the most seen clearly and real of its significant positive correlation within group of students daily life. The aim of developing SOLO Taxonomy instruments is measuring and analyzing the group of student ability to learn and master a concept in various point of views to accomplish its level of Piaget cognitive. This research is constructed based upon research and development which the trial phase was done on line and 40 SMAN 12 Surabaya students being sampled randomly, Data analysis method used was a validation method and tests which were then analyzed descriptively. The results of the development research of SOLO taxonomy-based assessment instruments on the Material of the Human Respiration system to measure thinking skills and mastery of theoretically validated concepts with an average value on the type of question A of 100% and the type of question B of 96% which can be interpreted into the category of very valid data. Empirically, the reliability value for type A questions was 0.69 (reliable / high) and type B questions is 0.68 (reliable / high); the value of the level of difficulty of the type A questions is 67% (moderate) and 33% (easy), in the type of question B is 84% (moderate) and 16% (easy); the value of the sensitivity of the questions with 100% sensitive questions on both types of questions. Keywords : assessment instruments, SOLO taxonomy, Human Respiratory System